SINERGI QURANI BERJEJAK SEBAGAI STRATEGI BRANDING SEKOLAH ISLAM BERBASIS NILAI - Kuntum Khairan Nisa; Mohamad Joko Susilo (STKIP Pesisir Selatan, 2026)
One approach strategy that can be developed is the Synergy of Quranic Traces, namely a strategy that places the values ​​of the Quran as the foundation of school culture and educational management, while also being realized in real actions through religious habits, integration of values ​​in learning, exemplary behavior of educators, and social involvement. This study proposes Sinergi Qurani Berjejak as a value-based branding strategy for Islamic integrated schools by bridging the divide between internal Qur’anic value internalization and institutional branding practices. Using a qualitative library research approach with content analysis of recent literature on Islamic education management and value-based branding, the study finds that embedding Qur’anic values as the core of school culture through cross-curricular learning, teacher role modeling, and sustained community engagement strengthens institutional identity, builds public trust, and increases parental interest. The integration of spiritual cultivation, dakwah, and social contribution enhances the competitiveness of Islamic schools in the digital era. This study formulates a concise conceptual framework that positions Qur’anic values not only as moral foundations of education but also as strategic assets for sustainable, value-based school branding with measurable social impact.